Human rights encounters in small places: the contestation of human rights responsibilities in three Dutch municipalities. Issue 2 (4th May 2019) - Miellet, Sara
Abstract: This article investigates engagements of local authorities with human rights in the field of irregular migration in a small town, medium-sized city and a rural municipality in the Netherlands. Although scholarship on human rights cities constitutes an important point of departure for this study, this article challenges the urban bias in this emerging body of research on the role of local authorities in processes of human rights localization. Drawing from theories of legal pluralism, scholarship on human rights practice and encounters and finally geographical insights, the article examines spatial dimensions of human rights practices of municipal actors in these three municipalities. More specifically, it investigates how in these municipalities the presence of and encounters with irregular migrants in local institutional spaces contribute to a local contestation of human rights responsibilities and examines how this process of contesting human rights responsibilities differs between these municipalities. The article draws on and develops scholarship on human rights encounters, by extending the scope beyond encounters at high seas and by explicating how power dynamics, temporalities and the sites of encounters can give rise to perceptions of duties that set these encounters apart from everyday sociabilities or encounters with difference. On the basis of a qualitative content analysis of municipal council documents and proceedings this study moreover found considerable differences with regard to how human rights responsibilities are contested locally by municipal actors. This study observed both differences among municipalities and differences among municipal actors within a single municipality in relation to these local understandings of human rights and perceptions of human rights responsibilities.